OXYGEN TRANSFER RATE IN THE THREE-PHASE FLUIDIZED BED BIOREACTOR WITH KMT BIOMASS SUPPORT WHEN USED IN INDUSTRIAL WASTEWATER TREATMENT PART 1: EFFECT OF AIR FLOW RATE - Manyele, S. V.; Halfani, M. R.; Sokol, W. (Tanzania Journal of Engineering and Technology, 2018)
Abstract